Healthy Eating Index-2015 and Predicted 10-Year Cardiovascular Disease Risk, as Well as Heart Age - Zhang, Yinyin; Lu, Cong; Li, Xinyu; Fan, Yameng; Li, Jiaqiao; Liu, Yamei; Yu, Yan; Zhou, Long (Frontiers in Nutrition, 2022)
Background and Aims Dietary factor plays an important role in the prevention of cardiovascular disease (CVD). The healthy eating index-2015 (HEI-2015), an indicator of the overall dietary quality, has been introduced to reflect adherence to the 2015–2020 Dietary Guidelines for Americans (DGA). This study aims to explore the associations of the HEI-2015 with predicted 10-year CVD risk and heart age among United States adults aged 30–74 years old using data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014. Methods and Results We conducted a cross-sectional analysis among 6,614 participants aged 30–74 years old. The HEI-2015 scores were calculated from 2-days 24-h dietary recall interviews. The 10-year CVD risk and heart age were derived from the sex-specific Framingham general cardiovascular disease risk score. We defined high cardiovascular disease risk as a predicted 10-year cardiovascular disease risk of > 20%. Multiple linear regression and binary logistic regression models were used to investigate the associations of the HEI-2015 with predicted 10-year CVD risk and heart age. Compared with participants in the lowest HEI-2015 quartile, those in the highest quartile had lower predicted 10-year CVD risk (β = −2.37, 95% CI: −3.09 to –1.65, P < 0.0001), lower heart age (β = −2.63, 95% CI: −3.29 to –1.96, P < 0.0001) and lower odds for high risk of CVD (OR = 0.62, 95% CI: 0.49 to 0.80, P-trend < 0.0001) after adjusting for multiple covariates. Conclusion Higher adherence to the 2015–2020 Dietary Guidelines for Americans is associated with lower predicted 10-year cardiovascular disease risk and lower heart age among United States adults.